Feeding practices and nutritional status of Mexican children affiliated to the Medical Insurance for a New Generation Prácticas de alimentación y estado de nutrición de los niños mexicanos afiliados al Seguro Médico para una Nueva Generación - Samuel Flores-Huerta; Miguel Klünder-Klünder; Onofre Muñoz-Hernández (Instituto Nacional de Salud Pública, 2012)
OBJECTIVE: To identify feeding practices and nutritional status in children affiliated to the Medical Insurance for a New Generation (SMNG). MATERIALS AND METHODS: An in-home survey addressed to mothers which included anthropometric measures of children; performed in March and April 2009 in Mexican States. RESULTS: The prevalence of any form of breastfeeding was (months) 6-11: 67.9%; 12-17: 43.6%; 18-23: 26.4%; >23: 16.7%; with higher figures in rural children. BF duration was eight months. Continued breastfeeding at 1 year of age was 43%. At 1 year of age, almost all children consumed fruits, vegetables, cereals and legumes; however, 13.5%-20.3% did not consume foods of animal origin, but ~84% and ~60% consumed fried and sweet foods and soft drinks. Nutrisano (a food supplement) was consumed by just 2/3 of the Oportunidades Children. Stunting and overweight were the predominant alterations of nutritional status. CONCLUSION: Improving the nutritional status of children affiliated to the SMNG requires promotion of appropriate healthy dietary practices and the surveillance of infant growth. OBJETIVO: Conocer las prácticas de alimentación y estado nutricio de niños protegidos por el Seguro Médico para una Nueva Generación (SMNG). MATERIAL Y MÉTODOS: Encuesta en hogares realizada en marzo y abril de 2009 en los diferentes estados de México. RESULTADOS: La prevalencia de lactancia materna fue (meses) 6-11: 67,9%; 12-17: 43,6%; 18-23: 26.4%;> 23: 16,7%, la duración fue ocho meses. La lactancia materna continuada a 1 año fue 43%. Al año, casi todos los niños consumen frutas y verduras, cereales y leguminosas, pero los de origen animal no están consolidados. Una gran proporción de niños de un año consume alimentos potencialmente obesogénicos; 2/3 de los niños de Oportunidades consumen Nutrisano. El retraso del crecimiento y el sobrepeso fueron las alteraciones predominantes del estado nutricional. CONCLUSIÓN: Mejorar el estado nutricional de los niños afiliados al SMNG requiere la vigilancia de indicadores de prácticas de alimentación y de su crecimiento.